Risks and Benefits of Helicobacter pylori Eradication: Current Status. (2002) - Hunt, Richard H; Fallone, Carlo; van Zanten, Sander Veldhuyzen; Sherman, Phil; Smaill, Fiona; Thomson, Alan BR; the Canadian Helicobacter Study Group,
Abstract : In patients with diseases known to be associated with Helicobacter pylori infection, such as peptic ulcer, treatment of the underlying infection is the standard of care. However, in most major consensus management guidelines, including those published in Canada, widespread testing for H pylori infection is not recommended. This practice is not encouraged because of insufficient evidence of cost-benefit in gastric cancer prevention, the potential for increases in antibiotic resistance and the controversial hypothesis of potential negative effects of eradication in certain clinical entities. For example, there is insufficient evidence to recommend against eradicating H pylori discovered in a patient with symptoms of gastroesophageal reflux disease. The management guidelines designed specifically in Canada should, therefore, continue to be applied, with H pylori diagnosed and treated in appropriately selected patients.